К методике определения относительного роста частей тела животных - Самарский, С.Л.; Передрий, В.Р. (Вестник зоологии, 1978)
A formula is suggested to recalculate the equation y=axᵇ for the rate of a relative growth of certain parts or organs of the animal body. It is shown how a relative growth changes during ontogenesis. Rightfulness of the allometric growth equation application to the weight groups of animals is disputable. Analytical and empirical functions of y=f(x) are compared and methods are suggested to calculate the relative growth rates from empiric curves.